The United Nations Global Compact: What Did It Promise? - Williams, Oliver F. (Journal of business ethics, 2014)
Sethi and Schepers (J Bus Ethics, 2014, in this Thematic Symposium) have identified an important issue for the global economy: Providing some mechanism for requiring assurance that environmental, social, and corporate governance information provided by a business is accurate and objective. Where they have gone wrong is in trying to change the mission of the United Nations Global Compact (UNGC). From its inception, the UNGC has been clear that its mission is not to provide such assurance. This article first outlines the background for the historic announcement of the UNGC by the then Secretary-General of the UN, Kofi Annan. Then a summary of the major criticisms of the initiative is provided with a focus on the Sethi–Schepers article. Finally, I argue that the mission of the UNGC, to gain consensus in the global community on the shared values and moral norms that will guide the global economy, is being accomplished, although it is a work in progress.